Raspberry Pi with Java programming the internet of things (IoT) - Chin, Stephen; Weaver, James L. (McGraw-Hill Education, 2016)
"Create embedded projects for personal and professional application. Join the Internet of Things revolution with a project-based approach to building embedded Java applications. Written by recognized Java experts, this Oracle Press guide features a series of low-cost, DIY projects that gradually escalate your development skills. Learn how to set up and configure your Raspberry Pi, connect external hardware, work with the NetBeans IDE, and write and embed powerful Java applications. Raspberry Pi with Java: Programming the Internet of Things (IoT) covers hobbyist as well as professional home and industry applications." --Back cover
Contains index, pages 297-315
Baking Pi -- Your first Java project -- Binary timer -- IoT hat -- Line runner -- Tea station -- Autonomous drone -- Retro video game emulator -- Nighthacking RetroPi -- Index
Keywords: Embedded computer systems / Programming; Raspberry Pi (Computer); Java (Computer program language); Internet of things; Programmierung; Java -- Programmiersprache; Raspberry Pi